Self-reported Barriers to Regular Dental Care in Chennai, Tamil Nadu - Nandhini, L; Barani, K; Prabu, D; Manipal, Sunayana; Ahmed, Adil; Adusumilli, Preethi (Journal of Orofacial Research, 1970)
Aim: The aim of this study was to assess the self-reported barriers to regular dental care in Chennai city, Tamil Nadu. Materials and methods: The cross-sectional study was doneon 352 people, aged 18 to 60 years in Chennai, Tamil Nadu. The study included 154 males and 196 females. The samples were selected by stratified random sampling and a 10 itemquestionnaire was given. Level of significance was set at